Drivers of unemployment intensity in sub-Saharan Africa: Do~government intervention and~natural resources matter? - Olawale Daniel Akinyele; Olusola Mathew Oloba; Gisele Mah (Review of Economics and Political Science (REPS), 2023)
Purpose - African countries are endowed with both human and natural resources. These resources constitute integral components for any economic development due to the long-lasting relationship with all sectors in an economy, yet there is an obvious disagreement between growing economy and employment generation in Africa. Though there has been a growing pattern of economic size, particularly the gross domestic product (GDP) among African countries, most of these economies are low in human development. The disagreement between economic growth and employment generation in Africa despite abundant natural resources located on the continent calls for public discourse among scholars. Therefore, the purpose of the study is to examine the peculiar drivers of unemployment intensity in a region characterized by endowed resources. Design/methodology/approach - The paper adopts two approaches; the authors employed the pooled mean group (PMG) estimator and utilised stochastic frontier analysis (SFA) to generate a government efficiency index between the period 1991 and 2017 among sub-Saharan Africa (SSA) countries. Findings - The empirical results through the single output-multiple inputs framework indicate that on average, there is a low level of government efficiency towards increasing the objective of human development in Africa. However, in the long run, natural resource endowment has a positive and significant relationship with employment generation for SSA. Hence, the study established that a low level of government efficiency has a long-lasting effect on low human development experienced in Africa. Social implications - The need to improve the level of government efficiency towards economic development by making both human and physical capital more effective will spur the exploration of natural resources. Originality/value - The paper provides an empirical study of the effectiveness and efficiency of government through PMG and SFA in establishing the relationship between government approaches and employment level in selected SSA countries.
Keywords: 330; Efficiency; Government expenditure; Human development; Natural resources; Unemployment